Prevalence of Portopulmonary Hypertension in Patients with Hepatic Cirrhosis - Sandhu, Umar Javaid; Chaudhary, Ayesha; Jami, Ahmad Salman; Wajid, Hafiz Bilal; Shakeel, Farah; Seira, Gull (Indus Journal of Bioscience Research, 2025)
Objective: “To determine the frequency of portopulmonary hypertension in patients with hepatic cirrhosis.” Study Place and Duration: Department of Medicine, Ghurki Trust Teaching Hospital, Lahore for 05 months from 7th Feb 2025 to 8th June 2025. Methodology: After meeting the selection criteria, 130 patients were and underwent portal vein Doppler ultrasound and echocardiography. Portopulmonary hypertension was diagnosed if the patient had a tricuspid regurgitation velocity ≥2.8 m/s, an estimated pulmonary artery systolic pressure >35 mmHg on echocardiography, pulmonary arterial pressure >20 mmHg, pulmonary artery wedge pressure ≤15 mmHg, and pulmonary vascular resistance ≥3 Wood units. All findings were documented in a structured proforma and analysed in SPSS. Results: The mean age of participants was 55.40 ± 9.76 years. Among them, 71 (54.6%) were male and 59 (45.4%) were female. In this study, porto-pulmonary hypertension was observed in 14 patients (10.77%) with hepatic cirrhosis. Among males, 4 (5.6%) had portopulmonary hypertension, compared to 10 (16.9%) females (p = 0.038*). Conclusion: Based on the findings of this study, it can be concluded that portopulmonary hypertension was present in 10.77% of patients with hepatic cirrhosis, with a higher prevalence observed among females.